Developing heritage tourism using (SWOT) as a tool to identify strategic alternatives. A case study in Bou-Saada - Dahmani, Brahim; Hadjab, Makhloufi (Technium Social Sciences Journal, 2023)
Understanding and analyzing heritage environments as a major driving force for tourism development, especially in developing countries, is of great importance to decision makers in program operations and revitalization and development plans. As well as determining the requirements for its activation (within an integrated framework), in order to establish a balanced model for tourism development. In this paper, a SWOT analysis study was used to formulate tourism growth strategies for the city of Bou Saada. To reach the most important strengths, weaknesses, opportunities and threats - the analytical hierarchy process. As one of the most important and widely used strategic analysis tools. The most dangerous factors for tourism development in these heritage environments is the deterioration of the environmental situation in all its forms, erosion and distortion of the image of its ancient fabric. Weaknesses are the second priority factor in the growth of its tourism. The weakest factor for these tourist destinations is the lack of tourism product and unplanned development. Besides, the natural beauty of the Bou Saada oasis and its biodiversity is the most enhanced aspect, such as: eco-tourism resorts, giving way to these destinations. It also has opportunities for more employment options, as well as for the local population, while at the same time contributing to the growth of the local infrastructure.